A utilitarian measure of economic growth - Dan Usher (Queen's University, Department of Economics, 2016)
A utilitarian measure of economic growth combines changes in the distribution of income with changes in real income per person to show how much better off people are becoming over time. It is the rate of growth of the dollar value of average utility of income. As such , it is seen differently by people with different utility of income functions. A growth rate in U.S. household income of 0.63% per year as ordinarily measured disappears altogether - is transformed into a decline of 0.086% per year - when the utility of income function is sufficiently concave. Strengths, weaknesses and implicit assumptions of the utilitarian measure are discussed.
Keywords: E31; E32; O40; 330; national income; utilitarian; certainty-equivalence